/Unsaying ***/ Peut-on se dédire du genre ? - Julie Abbou (Glad!)
In grammatically gendered languages, gender is simultaneously a structural categorisation and a power relationship. In this case, what linguistic room of manoeuvre do we have to challenge gender ? How to say (or unsay) gender ? In French, gender is a compulsory grammatical category. Yet, there is plenty of means to bypass this requirement, to unsay, distort or non-conform gender obligations. What is this linguistic turmoil the sign of ? Does it means that a compulsory gender might not be necessary, or at least, not mandatory ? Two approaches, which are very distinct at first sight, may help us understand this bypassing of gender obligation : Taoism and Rhetoric. They both fathom language as a space of contradiction, within which various qualifications of gender can freeze or unfreeze, in the light of plural norms. They also share the possibility to critique these norms and doxa of gender. In this light, Taoism and Rhetoric are two complementary faces of a common understanding of language as an activity.